Ottoman court ceremonies and the multiple ceremonial center - Peksevgen, Şefik. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
This study, titled as "Ottoman Court Ceremonial and The Multiple Ceremonial Center", attemptes to investigate the ceremonial borders of the Ottoman Court. The second concern of this study is to look for a ceremonial center in these borders and then is to show the flowing nature of this center which will be called Multiple Ceremonial Center at the end of the study. The time which this study concentrates on is the last three decades of the eighteenth century. When the archival documentation is available and pertaining to the context of the study, first two decades of the nineteenth century and some references to the sixteenth are included. The first chapter deals with the archival documentation pertaining to the subject. In this chapter, content and the frequency of the documentation and the method they were used in this study are disclosed. The second chapter deals with certain examples of the Ottoman Court Ceremonial. This chapter gives descriptions of the some main ceremonial performances that take place in the Ottoman Court. The final chapter of the study attempts to draw the borders of the space where these ceremonies are performed and to show that the political gravity is centered differently during the ceremonies. The appendix section includes the archival documentation used for this study.